Natural Disasters Occurrence, Reduction, and Restoration in Mountain Regions (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Mountain regions are critical because of their diverse geological conditions, dynamic changes, and the multiple natural hazards that often occur. Mountains are high-risk environments that can experience a variety of natural hazards, since initiated hazards often trigger secondary, cascading hazards, having a significant impact not only on the area of occurrence but often also on up- and downstream regions. High economic losses and human casualties are caused by geophysical (rockfalls, earthquakes, and volcanic activities), hydrological (floods, avalanches, and dammed-lake outbursts), and sediment-related hazards (landslides, driftwood, debris/mud flows, and surface erosion). Under the impacts of global warming and climate change, the spatiotemporal patterns of rainfall and other weather events have become more unevenly distributed, often with a more extreme magnitude and/or intensity of events. The complexity of mountainous regions, in addition to the continued changes in climate and land use, have made it more challenging to predict mountainous hazards and their impacts on communities. Based on the countless efforts made worldwide on natural hazards in mountain regions, tight international collaboration is strongly required to answer questions related to the causes of disasters, the monitoring of hazardous phenomena, predicting disasters, and the effective reduction of hazardous consequences.